(untitled) (Canadian Eye Care Today, 2025)
Pars plana vitrectomy (PPV), introduced by Dr. Robert Machemer in the 1970s, revolutionized the treatment of vitreoretinal diseases. Technological advancements, such as the development of small-gauge instrumentation and wide-angle viewing systems, have since enhanced the precision and safety of these procedures. However, microscope-based visualization remains limited in scenarios involving limited anterior segment transparency, or when accessing anatomical areassuch as the anterior vitreous base, ciliary body, and retroirideal space. Endoscopic vitrectomy overcomes these limitations by offering direct intraocular imaging from the probe tip, bypassing anterior segment opacities, and yielding an unobstructed, distortion-free view of otherwise hidden structures (Figure 1). This technique allows for dynamic adjustment of perspective and orientation, enabling access to the peripheral retina, anterior vitreous base, and retroirideal structures not easily visualized with traditional top-down microscope-based views (Figure 2 and Table 1). Modern endoscopy systems combine miniaturized probes, high-resolution video capture, coaxial illumination, and enhanced manoeuvrability, making them valuable tools in both routine and complex cases. This review explores the evolving role of endoscopic vitrectomy by examining its principles, instrumentation, clinical applications, surgical techniques, limitations, and future directions—demonstrating how a shift in visual perspective can broaden the capabilities of modern vitreoretinal surgery.